A novel cerebrovascular drug-coated balloon catheter for treating symptomatic intracranial atherosclerotic stenosis lesions: Study protocol for a prospective, multicenter, single-arm, target-value clinical trial - Qianhao Ding; Wenbo Liu; Jingge Zhao; Dehua Guo; Yao Tang; Tengfei Zhou; Yanyan He; Ferdinand K. Hui; Yonghong Ding; Liangfu Zhu; Zilang Wang; Yingkun He; et al. (Journal of Interventional Medicine, 2023)
Background: Previous single-center studies have demonstrated that drug-coated balloons (DCBs) may reduce restenosis rates, which is an important factor affecting the prognosis for intracranial interventional therapy. However, currently available cardiac DCBs are not always suitable for the treatment of intracranial atherosclerotic stenosis (ICAS). This study aimed to evaluate the safety and efficacy of a novel DCB catheter designed for patients with severely symptomatic ICAS. Methods: This prospective, multicenter, single-arm, target-value clinical trial was conducted in 9 Chinese stroke centers to evaluate the safety and efficacy of a novel DCB catheter for treating symptomatic severe ICAS. Primary metrics and other indicators were collected and analyzed using SAS version 9.4 (SAS Institute, Cary, NC, USA). Results: A total of 155 patients were enrolled in this study. The preliminary collection of follow-up data has been completed, while data quality control is ongoing. Conclusion: Results of this study demonstrated the patency rate, safety, and effectiveness of a novel on-label paclitaxel DCB designed for the treatment of ICAS. Trial registration: ChiCTR, ChiCTR2100047223. Registered June 11, 2021-Prospective registration, https://www.chictr.org.cn/ChiCTR2100047223.